Violence and mental health : opportunities for prevention and early detection: proceedings of a workshop - Patel, Deepali (Online access: NCBI NCBI Bookshelf., 2018)
On February 26-27, 2014, the National Academies of Sciences, Engineering, and Medicine's Forum on Global Violence Prevention convened a workshop titled Mental Health and Violence: Opportunities for Prevention and Early Intervention. The workshop brought together advocates and experts in public health and mental health, anthropology, biomedical science, criminal justice, global health and development, and neuroscience to examine experience, evidence, and practice at the intersection of mental health and violence. Participants explored how violence impacts mental health and how mental health influences violence and discussed approaches to improve research and practice in both domains. This publication summarizes the presentations and discussions from the workshop.